Engenharia de biocatalisadores aplicada à síntese de CLEAs para a aplicação na conversão multienzimática de sacarose à ácido glucônico e xarope de frutose - Mafra, Agnes Cristina Oliveira (Universidade Federal de São Carlos, 2017)
Sugarcane sugar (sucrose) is a raw material produced in abundance in Brazil; it is very attractive to produce high added-value products. Gluconic acid (GA) can be obtained by multienzymatic conversion of sucrose, using three enzymes. Firstly, invertase (INV), responsible for the inversion of sucrose into glucose and fructose, next glucose oxidase (GOD) for the glucose oxidation and the last enzyme is catalase (CAT) used for the decomposition of hydrogen peroxide (H2O2, by-product from glucose oxidation). In this study, the sucrose was inverted in a fed-batch process catalyzed by INV immobilized as cross-linked enzyme aggregate (CLEA). The GA was produced by glucose oxidation catalyzed by combinate CLEAs (Combi-CLEAs) of CAT from bovine liver and GOD from Aspergillus niger in a batch pneumatic reactor. CAT has a tetrameric structure which complicates its stabilization through conventional immobilization technique. CLEAs of CAT were prepared, evaluating the effect of precipitant and cross-linking agents, as well as bovine serum albumin (BSA) as feeder protein on the catalytic properties, thermal stability, and mass transport resistance of the derivatives. The most active derivatives were prepared using ammonium sulfate as precipitant agent, 50 mM glutaraldehyde as cross-linker, and BSA/CAT mass ratio of 3.0. These derivatives were almost completely active (yield of immobilization up to 100%) and highly stable at 40 oC and pH 7.0 (~ 80% of the initial activity was recovery after 200 h under these conditions). The co-precipitation of BSA together with CAT reduced the size of clusters suggesting a decrease of diffusive effects within the biocatalyst. Empirical kinetic model was fitted to the experimental data of initial rate vs. substrate concentration and used to make a comparative analysis of mass transfer into derivatives with and without BSA. Results suggested that the main effect that differentiates the free enzyme and the two derivatives analyzed was of diffusive nature. In fact, the effectiveness factor of the crosslinked aggregates of catalase with BSA increased approximately 4 times. The statistical experimental design and the analysis of the response surface methodology showed that the immobilization did not alter the conditions of maximum activity of the CAT, which were found to be 30 oC and pH  7.0 for all biocatalysts. Secondly, INV was immobilized by CLEA methodology using soy protein as feeder molecules as an alternative to the commonly used expensive BSA. The immobilized INV retained around 30% of the initial activity after enzyme leaching assay. The immobilized INV was recycled tenfold in 4 h-batches of hydrolysis of sucrose at 40 oC and pH 6.0, maintaining the reaction conversion above 75 %. The hydrolysis of sucrose catalyzed by immobilized INV showed to be economically feasible in an operational window built based on economic metrics for a fed-batch process with three intermittent sucrose feeds to restore the substrate concentration at 100 g.L-1 when the conversion reaches 95 %. This work represents an advance in the field, because using a carrier-free and recyclable biocatalyst the specific productivity (gram of products per gram of biocatalyst per hour) of inverted sugar syrup was as high as those previously reported for INV immobilized on solid carriers that may dilute its volumetric activity and increase the cost of the biocatalyst. Combi-CLEAs of CAT and GOD were prepared, evaluating the influence of precipitant and cross-linking agents, as well as BSA as feeder protein on enzyme immobilization yield and thermal stability of each enzyme. Combi-CLEAs were prepared using dimethoxyethane as precipitant, 25 mM glutaraldehyde and mass ratio BSA/enzymes of 5.45 (w/w) were selected, their activities and stabilities at 40 oC, pH 6 and 250 rpm for five hours were evaluated. The selected Combi-CLEAs were used in GA production in a pneumatic reactor with 26 g.L-1 glucose at 40 oC, pH 6 and 10 vvm. Results showed conversion of 100 % and kinetic profile very similar to the free enzymes process. The reusability of Combi-CLEAs was also studied in ten batch-cycles of 5 hours. Operational half-life was calculated from kinetic profiles and first order inactivation model and presented a value of 31.50 hours. Combi-CLEAs of GOD and CAT showed to be relevant robust biocatalyst for GA application and production of glucose.
Biocatalyst engineering applied to the improvement of cross-linked enzyme aggregates aiming at the multienzymatic conversion of sucrose to gluconic acid and fructose syrup
Keywords: Ácido glucônico; Açúcar invertido; Proteína de soja; Engenharia de biocatalisador; Gluconic acid; Inverted sugar; Soy Protein; Biocatalyst engineering; ENGENHARIAS::ENGENHARIA QUIMICA